Fast in vivo quantification of T1 and T2 MRI relaxation times in the myocardium based on inversion recovery SSFP with in vitro validation post Gd-based contrast administration - Karmonik, Christof; Malaty, Adam; Bikram, Malavosklish; Schmitt, Peter; Partovi, Sasan; Shah, Dipan J. (Cardiovascular Diagnosis and Therapy, 2014)
Purpose: A fast clinical imaging technique for quantifying myocardial T1 and T2 relaxation times after Gadolinium (Gd)-based contrast administration within a single breathhold is presented with in vitro validation. Materials and methods: From signal intensity curves in ECG-gated segmented inversion recovery balanced steady state free precession (IR-bSSFP) images, T1 and T2 values were determined for 24 agarose samples made from solutions of Omniscan (0.25-2 mg/mL) and copper-sulfate (0.52-22.17 mg/mL). T1 and T2 were also measured using turbo spin-echo (TSE) acquisitions and compared with IR-bSSFP results. In vivo T1 and T2 values from post-contrast IR-bSSFP images of five healthy volunteers were determined for (I) the left ventricular wall, (II) the interventricular septum (IVS) and (III) the lateral wall of the left ventricle (LV). Spin system simulations were performed for selected T1 and T2 values. Results: Good agreement between TSE and IR-bSSFP for T1 for realistic in vivo post-contrast values (below 1,250 ms, R=0.88) and for T2 (entire range, R=0.97) was found. Spin system simulations were in good agreement with measurements. In vivo average T1 was 546±32 ms and average T2 was 59±9 ms. Conclusions: A fast imaging protocol for absolute quantification of myocardial T1 and T2 post-contrast is presented, validated in vitro and consecutively applied in vivo in humans.